Moral Philosophy in the Qur’an From theViewpoint of the Risale-i Nur Said Nursi - Jamal Ahmad Sa’id al-Marzuqi (TSAQAFAH, 2013)
The  content  of  moral  philosophy  in  Risale-i  Nur Said  Nursi  which  is derived from the Qur’an is abundant. This paper is an attempt to elaborate that moral philosophy of the Qur’an explained thoroughly in Risale-i Nur. The topics discussed here include the idea that evil is not fundamental to the world; it is only a means of knowing good, while men are the source of moral evil. In the Risale-i Nur, Nursi describes the hardships of his life in exile, the difficulties he suffered, and the distress he felt at the inhuman treatment meted out to his brothers, his country, and all humanity even. It is because what regarded as evil such as death is actually an instance of good and the gate of mercy. The plausible question is whether man is free to do and to desire something. For Nursi it is obvious that human freedom can be conducted only within the limits of divine determination.  Nursi  compares  the  wisdom  of  the  Qur’an  and  that  of philosophy,  the  training  and  education  both  offer  to  mankind.  One  of  the things the Risale-i Nur teaches us is that what we suppose to be life is in reality only a small slice of time. Because for us, the past and future are non-existent and dead.